Natural IgM attenuate formation of neutrophil extracellular traps induced by oxidation-specific epitopes in vitro and in vivo. (3rd October 2022) - Ondracek, A; Afonyushkin, T; Taqi, S; Aszlan, A; Koller, T; Hofbauer, T M; Ozsvar-Kozma, M; Sharma, S; Scherz, T; Beitzke, D; Testori, C; Lang, I M; et al.
Abstract: Background: Neutrophil extracellular traps (NETs) emerged as important drivers of thrombus formation in acute myocardial infarction (AMI). Therefore, mechanistic understanding of inducers and modulators of NETosis at the site of occlusion is pivotal for new diagnostic and therapeutic approaches. Many triggers of NET formation have been described, among them oxidations-specific epitopes (OSE), products of lipid peroxidation. Extracellular vesicles (EV) carrying OSE are elevated in AMI. OSE-EV can be recognized by natural IgM antibodies exerting protective functions in cardiovascular disease by reducing the pro-inflammatory response to OSE. Purpose: We hypothesized that EV-induced NET formation could be dampened by OSE-IgM in vitro and in vivo. Methods: Patients were recruited after diagnosis of ST-segment elevation myocardial infarction (STEMI, n=51). Blood was aspirated from the culprit site during percutaneous coronary intervention and at several follow-up time points. Myocardial function was assessed by cardiac magnetic resonance (CMR) at 72 hours and 6 months. EV were isolated by ultracentrifugation and characterized by flow cytometry staining for CD45, CD41a, CD144, and OSE. Isolated EV were used for neutrophil stimulation in vitro and in vivo employing a murine injection model. NETs were visualized by immunofluorescence, staining for DNA, histones, citrullinated histone 3, and myeloperoxidase. NET markers and natural IgM recognizing OSE (OSE-IgM) in murine and patient plasma were measured by ELISA. Results: EVs of endothelial, leukocyte, and platelet origin revealed a prominent absolute and relative increase of the OSE-carrying population as recognized by the malondialdehyde-specific antibody LR04. Plasma derived from the site of occlusion contained more and proportionally higher levels of OSE-EV derived from CD45+ cells than the intra-patient peripheral control. No difference was observed for EV of platelet origin, and the endothelial-derived subset of OSE-EV was decreased at the culprit site. OSE-EV and NET markers were positively associated in the circulation. Decreasing OSE-IgM levels during hospital stay indicated consumption of protective antibodies. EV isolated from AMI patient plasma were revealed to induce NET formation in neutrophils in vitro and after injection into mice in vivo, as measured by cell-free DNA and fluorescence microscopy of citrullinated histones in neutrophils. The LR04 IgM antibody, but not a control IgM, reduced the NETogenic effect of EV in both models. Consistently, higher circulating levels of EV and lower OSE-IgM were associated with a reduced ejection fraction in AMI patients at 72 hours and six months. Conclusion: EV from AMI patients induced NETosis in vitro and in vivo. IgM recognizing malondialdehyde-epitopes diminished this effect indicating that the balance between OSE-EV and OSE-IgM during AMI may represent a potential prognostic and therapeutic target with impact on heart function. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Vienna Science and Technology Fund (WWTF)